2016
DOI: 10.1016/j.gore.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Small cell ovarian carcinoma: Long term survival in juvenile case with poor prognostic features

Abstract: BackgroundOvarian small cell carcinoma is a rare, aggressive neoplasm that occurs in young women and has a poor long-term prognosis. Treatment involves surgical resection and chemotherapy. The required radicality of surgery is uncertain, balancing cytoreduction with fertility preservation. Various chemotherapy regimens are utilized due to confusion regarding the neoplasm's lineage.CaseWe describe an adolescent with small cell carcinoma, hypercalcemic type, stage IA. Surgery included left salpingo-oopherectomy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Given these factors, the optimal surgical approach is not yet well-defined and has been suggested that fertility-sparing treatment, such as unilateral oophorectomy, may be preferable [ 2 ]. In recent years, researchers have observed no better outcomes and higher complication and mortality rates associated with lymphadenectomy [ 32 ], and other studies have also indicated the potential for fertility-sparing surgical options in early-stage cases [ 33 34 35 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given these factors, the optimal surgical approach is not yet well-defined and has been suggested that fertility-sparing treatment, such as unilateral oophorectomy, may be preferable [ 2 ]. In recent years, researchers have observed no better outcomes and higher complication and mortality rates associated with lymphadenectomy [ 32 ], and other studies have also indicated the potential for fertility-sparing surgical options in early-stage cases [ 33 34 35 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal surgical approach is unknown, but since unilateral disease is present in most cases, Young et al suggest that fertility-conserving therapy, a USO, might be preferable in this young patient age group [5]. Other studies also suggest that there may be room for fertility-conserving surgery in the early stages [1,22,31,39,52,55]. Furthermore, Pressey et al recommend a limited diagnostic procedure followed by an intensive chemotherapy regimen and a second-look operation [2].…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used regimen was VPCBAE for the first-line treatment of advanced SCCOHT [20]. It should be noted that the VPCBAE regimen is associated with severe toxicities compared to bleomycin, etoposide, and cisplatin (BEP) [55]. Blanc-Durand et al confirmed the efficacy of the PAVEP regimen in combination with optimal cytoreductive surgery, achieving a complete response for 89% of the patients, particularly for 80% of the patients with residual disease [68].…”
Section: Discussionmentioning
confidence: 99%
“…Small cell carcinoma of the ovary pulmonary type (SCCOPT) remains an unusual and highly aggressive malignant neoplasm ( Kurasaki et al, 2013 ). The majority of cases are diagnosed at stage III-IV and it often affects older women ( Stewart et al, 2016 ). Current reports suggest a high case fatality rate regardless of stage at diagnosis ( Kurasaki et al, 2013 , Stewart et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cases are diagnosed at stage III-IV and it often affects older women ( Stewart et al, 2016 ). Current reports suggest a high case fatality rate regardless of stage at diagnosis ( Kurasaki et al, 2013 , Stewart et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%